2014
DOI: 10.1097/hjh.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and LDL-cholesterol targets for prevention of recurrent strokes and cognitive decline in the hypertensive patient

Abstract: It has been calculated that 925 patients would reach the primary outcome after a mean 4-year follow-up, and this should provide at least 80% power to detect a 25% stroke difference between SBP targets and a 20% difference between LDL-C targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 14 publications
2
23
0
5
Order By: Relevance
“…However, the “nadir” SBP values may possibly vary in hypertensive patients with different ethnic backgrounds or concomitant baseline diseases. We agree that the controversy of “the lower the better” versus the J curve can only be solved by a series of well‐designed randomized trials, such as the ongoing Stroke in Hypertension Optimal Treatment (SHOT) study 25. Nevertheless, our current findings emphasize that patients with grade 1 hypertension should possibly avoid excessive SBP reduction during treatment.…”
Section: Discussionsupporting
confidence: 58%
“…However, the “nadir” SBP values may possibly vary in hypertensive patients with different ethnic backgrounds or concomitant baseline diseases. We agree that the controversy of “the lower the better” versus the J curve can only be solved by a series of well‐designed randomized trials, such as the ongoing Stroke in Hypertension Optimal Treatment (SHOT) study 25. Nevertheless, our current findings emphasize that patients with grade 1 hypertension should possibly avoid excessive SBP reduction during treatment.…”
Section: Discussionsupporting
confidence: 58%
“…Investigators are able to prescribe a statin of their choosing and cognition is assessed using the Montreal Cognitive Assessment (MoCA) as a secondary outcome over 4 years of follow-up [193].…”
Section: On-going and Future Research Possibilitiesmentioning
confidence: 99%
“…16 However, there has been a relative paucity of data on the relationship of lower achieved SBP after stroke to mortality. [16][17][18] A recent analysis of long-term survivors of stroke 18 found that, compared with a reference SBP of 131 to 141 mm Hg, low SBP (≤120 mm Hg) measured 5 years after stroke was associated with an increased risk of all-cause mortality and the composite end point of recurrent stroke, myocardial infarction, or death over the ensuing 5 years. In contrast, neither patients with slightly lower SBP (121-130 mm Hg) or higher SBP (142-210 mm Hg) were at increased risk of dying or the composite end point.…”
mentioning
confidence: 99%